Preface of Special Issue - of Special Issue, Editor in Chief (Journal of Science and Technology, 2017)
The 3rd International Conference on the Application of Science and Mathematics (SCIEMATHIC2017) was held in Pagoh Educational Hub, Pagoh, Johor, Malaysia on August 24-25, 2017. The conference was organised by Faculty of Applied Sciences and Technology, Universiti Tun Hussein Onn Malaysia.Previous conferences took place successively in several places in Malaysia. The conference was started in 2007, formerly known as Seminar Kebangsaan Aplikasi Sains dan Matematik (SKASM2007) followed by the following year as Seminar Kebangsaan Aplikasi Sains dan Matematik (SKASM2008). In 2009, the seminar was co-organised with Faculty of Technical Education with the name of Persidangan Kebangsaan Pendidikan Sains dan Teknologi (PKPST2009). In the following year, the seminar was organised and named as Seminar Kebangsaan Aplikasi Sains dan Matematik (SKASM2010). In 2011, the conference was organised internationally as International Seminar on the Application of Science and Mathemathics (ISASM2011). In 2013, the seminar was organised nationally as Seminar Kebangsaan Aplikasi Sains dan Matematik (SKASM2013). In 2016, the seminar was rebranded as the 2nd International Conference on the Application of Science and Mathematics (SCIEMATHIC2016). This conference is now well established with a periodicity of one year. Starting from 2016, the SCIEMATHIC is expected to be organised every year either in Malaysia or ASEAN region.SCIEMATHIC2017 had successfully gathered 94 presenters. All the research works have been presented as oral presentations during the two days session. All accepted manuscripts were reviewed by expert reviewers in the related field and published in the Special Issue of Journal of Science and Technology (JST) which is indexed by Google Scholar and MyCite.This Special Issue of Journal of Science and Technology brings together insightful manuscripts that address issues related to Science and Mathematics. As Editor in Chief for the Special Issue of Journal of Science and Technology, I appreciate all authors who have provided good manuscripts and timely revisions in submitting their manuscripts. I would like to acknowledge and thank the reviewers for their valuable comments and timely efforts that greatly improved the quality of the published manuscripts. I am very grateful to the editors of the Special Issue of JST for their efforts, patience and editorial work during the publication of this special issue. Last but not least, I also like to thank Editor in Chief of JST, Dr. Ahmad Hadi Ali, for his support and providing assistance throughout the publication process of this special issue. I hope that the Special Issue of Journal of Science and Technology will serve as a valuable resource for the Science and Mathematics community.